Regenerative Effects of Three Types of Allografts on Rabbit Calvarium: An Animal Study - Amir Reza Rokn; Abbas Seyed Shakeri; Shahroo Etemad-Moghadam; Mojgan Alaeddini; Ahmad Reza Shamshiri; Rebecca Manasheof; Hamidreza Barikani (Frontiers in Dentistry, 2016)
Objectives: The aim of this study was to histologically compare the regenerative properties of two allografts manufactured by two Iranian companies.